Effect of inulin and xanthan gum on the properties of 3D printed Tartary buckwheat paste - Yaojia Li; Mantihal Sylvester; Ai Ling Ho; Jau-Shya Lee (IDEAS, 2024)
This work aimed to investigate the effect of inulin and XG on the 3D printability of Tartary buckwheat paste. A 2 × 3 factor design comprising three levels of inulin (6%, 10%, and 14%) and three levels of xanthan gum (XG) (0.4%, 0.8%, and 1.2%) was used. The effect of inulin and XG on the rheological properties (yield stress, flow behaviour, viscoelasticity, and creep-recovery property), 3D printed structure, and microstructure properties of Tartary buckwheat paste were investigated. Compared with the control sample, a high amount of XG (0.4% and 1.2%) shifted the ink to a more solid-like form and improved the consistency (K), mechanical strength (yield stress, storage modulus (G’)), resistance to deformation, and recoverability, while a high amount of inulin (14%) weakened these properties. Scanning electron microscopy (SEM) revealed that adding XG (0.4% and 1.2%) in the ink with 6% and 10% of inulin reinforced the ink structure. This study also identified the best combination of XG and inulin to facilitate the printing of Tartary buckwheat paste and produce a final product with an exquisite appearance. This study provided more insights for developing 3D printing of Tartary buckwheat foods rich in inulin.